КАРАЇМИ МЕЛІТОПОЛЬЩИНИ: ІСТОРІЯ ТА СУЧАСНІСТЬ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the research of history, culture and mentality features of caraim ethnic group which lives on the territory of East Tavriya and separately – in Melitopol Region. The social-culturalogical analysis of history of settling of caraim on the territory of Tavriya is conducted. The past and the present of culture and life of this etnos is explored.